Християнство в незалежній Україні перед викликами «нової релігійності» - Мосюкова, Н. Г.; Савченко, С. В. (НТУ "ХПІ", 2011)
Стаття присвячена критиці антихристиянських теорій, які з’явились в незалежній Україні в кінці ХХ ст. Охарактеризовані тенденції релегійного життя в сучасній Україні. Проведено порівняльний аналіз основних постулатів християнства та нових релігіозних течій.

Article is devoted criticism of Antichristian theories which have appeared (have revived) in the end of ХХ century, and also a problem of distribution of sectarianism in Post-Soviet Ukraine. Tendencies of religious life in modern Ukraine are characterized and the reasons of mass distribution of new totalitarian cults are defined. The comparative analysis of the basic postulates of Christianity and new religious associations is carried out. In article was attempt to define a place and a role of Christianity in the conditions of integration of Ukraine into globalization processes.
Keywords: церква; конфесія; духовність; теологія; культура; філософія; наука; віра; сектантство; культ